High temperature resistance of self compacting alkali activated slag/portland cement composite using lightweight aggregate - Dener, Murat; Karatas, Mehmet; Mohabbi, Mehrzad (Elsevier Sci Ltd, 2021)
The aim of this study was to fabricate self compacting alkali activated slag/Portland cement composite design by using of lightweight aggregate for high temperatures. Locally available pumice was used as lightweight aggregate. The four parameters considered in this study were: slag to cement ratio (GBFS: PC), water content, lightweight aggregate to normal aggregate ratio and alkali activator to binder ratio. After the tests carried out dependent on four parameters, six composite mixtures were determined for the high temperature experiment. For this purpose, the composite samples were exposed to temperatures of 200, 400, 600, 800 and 1000 degrees C and changes in compressive strength and ultrasonic pulse velocity were measured. The microstructural changes caused by the high temperatures were investigated by means of SEM and FTIR spectroscopy. Following the high temperature tests, compressive strength began to decrease with the temperature increasing. The minimum compressive strengths were observed at the temperature of 800 degrees C. At 1000 degrees C no further deterioration was observed in the compressive strength of the both PC-free and PC substituted composite mixtures. The temperatures at which the microcracks became more evident were 600 degrees C and 800 degrees C for the mixtures with 100% and 85% GBFS, respectively. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Alkali activated; Portland cement; Granulated blast furnace slag; Self-compacting; Lightweight; High temperature